Physical Evaluation and Stability of HPMC-Based Bromelain Enzyme Gel Preparation - Fira Irianti Umar; Mohamad Aprianto Paneo; Muhammad Taupik; Isha Isa; Ariani H Hutuba (Jurnal Literasi Mandiri, 2026)
Bromelain is a proteolytic enzyme derived from pineapple (Ananas comosus) and has potential as an active ingredient in topical preparations. The development of bromelain in gel form requires a suitable base to produce a preparation with good physical characteristics and stability. Hydroxypropyl methylcellulose (HPMC) was selected as the gel base because it can form a stable, homogeneous gel suitable for topical use. This study aimed to formulate and evaluate the physical characteristics and stability of an HPMC-based bromelain enzyme gel preparation. The study was conducted experimentally by optimizing HPMC gel bases at concentrations of 1%, 2%, and 3%. The selected base was used to prepare bromelain enzyme gel with bromelain concentrations of 2% (F1), 4% (F2), and 8% (F3). The evaluation included organoleptic properties, homogeneity, pH, viscosity, spreadability, adhesiveness, qualitative identification of bromelain, and stability using the temperature stress test method. The optimization results showed that 2% HPMC was the most suitable base, as it produced a homogeneous gel with pH, viscosity, spreadability, and adhesiveness values that met the requirements. The Biuret test was positive in pure bromelain and all gel formulas, indicating that bromelain protein remained detectable after formulation. Physical evaluation showed that all formulas were homogeneous, had a characteristic bromelain odor, and met the requirements for pH, viscosity, spreadability, and adhesiveness. The stability test showed no noticeable organoleptic changes in all formulas. However, pH and viscosity decreased as temperature increased, with the greatest viscosity reduction observed in F3. Based on the results, the HPMC-based bromelain enzyme gel preparation showed good physical characteristics, with 2% HPMC as the most suitable gel base. However, storage temperature should be considered to maintain the physical stability of the preparation.